Port designer's handbook - Thoresen, Carl A. (ICE Publishing, 2014)
'The Port Designer's Handbook', third edition provides practising port and harbour consulting engineers with essential guidance and recommendations for the layout, design and construction of modern harbour and port structures. The third edition is extensively revised and discusses various factors to consider when designing efficient container terminals.